Comparison of Saramis 4.12 and IVD 3.0 Vitek MS Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Identification of Mycobacteria from Solid and Liquid Culture Media - Leyer, Caroline (J Clin Microbiol, 2017)
During the last decade, many investigators have studied matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) for identification of mycobacteria. Diverse and contradictory results indicated that optimal level for routine testing has not been reached yet. This work aimed to assess Vitek MS through two distinct versions, Saramis v4.12 RUO and the IVD v3.0, under conditions close to routine laboratory practice. Overall, 111 mycobacterial isolates were subjected to protein extraction and same spectra were matched against both databases. The IVD v3.0 database proved to be superior to Saramis v4.12 and its identification rates remarkably increased, from 67% to 94% for isolates grown on Middlebrook 7H10 solid medium and from 62% to 91% for isolates grown on mycobacterial growth indicator tube (MGIT) liquid medium. With this new version, IVD v3.0, MALDI-TOF MS might be integrated into routine clinical diagnostics, although molecular techniques remain mandatory in some cases.